Fabrication of organic solvent nanofiltration membranes with graphene oxide - enhanced covalent organic framework via interfacial polymerization - Oor, Jia Zheng (2023)
Membrane-based filtration offers many benefits like lower energy consumption and operating cost for separation in harsh solvents. In particular, such membranes need to have high nanofiltration separation efficiency and high resistance to organic solvents. Unfortunately, the common thin film composite (TFC) - based organic solvent nanofiltration membranes often give low solvent permeance due to the dense skin layer atop the substrate. To address this, we fabricated a covalent organic framework (COF) - incorporated TFC membrane through the in-situ formation of benzene-1,3,5-tricarboxaldehyde (TFB) and graphene oxide (GO) in p-Cymene, a less toxic solvent, with p-Phenylenediamine (PPD) in aqueous phase via interfacial polymerization. The PES-COF-GO membranes exhibited optimal solvent permeance and separation efficiency at an intermediate 0.8wt% GO, which gave the highest water permeance of 16.2L/m2 h bar and a molecular weight cut-off (MWCO) of around 325 gmol-1. In addition, the crosslinked GO-COF layer endowed the membrane with chemical stability in non-polar solvents. The mechanical strength of PES-COF-GO membrane was also improved due to the COF-GO layer atop the PES substrate making the surface tighter and mechanically stronger.